Contrasting the genetic architecture of cardiac glutathione against other organs: unveiling a unique tissue-specific locus - Jessica Strosahl; Susan McClatchy; Gary A. Churchill; Rebecca L. Koch; Steven W. Craig; Robert Pazdro (Mammalian Genome, 2026)
Glutathione is a ubiquitous antioxidant with critical roles in xenobiotic clearance and aerobic metabolism. Reduced glutathione (GSH) is converted to its oxidized counterpart, GSSG, in the process of neutralizing free radicals and maintaining biochemical homeostasis. An imbalance between free radical generation and antioxidant protection leads to oxidative stress and diminished GSH concentrations. Polymorphisms in GSH synthesis and metabolism genes have been associated with cardiovascular disease (CVD) development and progression, highlighting the critical need to explore the link between GSH system genetics and CVD. While those prior studies have focused on canonical GSH genes such as glutathione peroxidases ( GPx ), few studies to this date have investigated whether genes outside of traditional GSH pathways may be impacting the cardiac GSH redox system. Here, we performed high-precision genetic mapping using the Diversity Outbred (DO) mouse stock which revealed novel loci and genes underlying the cardiac GSH system. Mapping results indicated a locus on murine chromosome 14 at 54.240 Mbp associated with cardiac GSH concentrations, and bioinformatics analyses delineated five potential candidate genes: Slc7a7 , Myh6 , Myh7 , MiR-208a , and Nfatc4 . In addition, statistical analyses revealed notable variation in the cardiac GSH redox system under normal physiological conditions and correlations between cardiac and renal GSH phenotypes in the same cohort of mice. Overall, these findings expand our current knowledge of the vital GSH system, reveal novel genetic regulation of cardiac GSH status, and present candidate genes to be tested in future mechanistic studies.